Wireless data communications: a study of bit error rate, modulation type and signal speed / Deepak K. Ghodgaonkar, Hadzli Hashim and Norasimah Khadri - Ghodgaonkar, Deepak K.; Hashim, Hadzli; Khadri, Norasimah (2000)
Wireless data communications (WDC) services such as wireless local area networks (WLANs), wireless access to internet, remote weather stations, wireless telemetry systems, provides flexibility and freedom for communication of information between people, personal computers (PCs) and machines. Due to WDC systems, it is possible to move around notebook computers and portable data terminals as long as they are within the coverage area of the wireless hub/server. For this study, we have developed a WDC system using portable two-way radios (walkie-talkie), voice-band modems and PCs. It is a low-cost and low-speed (less than few kilobits per second) WDC system with a range of 2-4 kilometers. In this report, we are reporting measured end-to-end bit error rate (BER), block error rate (BLER) and error free second (EFS (%)) for the WDC system at different distances (0-300 meters) and at various relative noise levels (0 to, 10).